Physical education learning outcomes: Does it have a correlation with nutritional status, physical activity, and students' cognitive function? - Tarigan, Beltasar; Lardika, Rola Angga (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2023)
The process of learning physical education in schools is influenced by nutrition, physical activity, and students' cognitive functions. The purpose of this study was to find out how students' nutritional status, physical activity, and cognitive function relate to their performance in physical education classes at school. This type of research is called correlational research. 98,289 junior high school students in Bandung, West Java Province, became the study population. Simple random sampling strategy for sampling 1870 students into the research sample. This study uses primary data provided from students' assessments of nutritional condition, physical activity, and cognitive function and secondary data provided from physical education teachers. The data collection method was in the form of a questionnaire to measure cognitive function, physical activity, and nutritional status, as well as student test scores from teachers to measure learning outcomes. Correlation analysis and multiple regression, as well as the F test, were used as data analysis methods in this study. Data analysis through computerized procedures using the SPSS application The tests needed are the normality test and the linearity test before testing the hypothesis. The findings demonstrate a significant correlation between learning outcomes and nutritional status, physical activity, and cognitive function. However, it is important to note that the research scope was limited to the field of physical education and the selected research subjects. Nonetheless, these results contribute to existing knowledge and can serve as a guide for future studies, particularly in the domain of physical education, aiming to optimise learning outcomes.